PERTAHANAN ASIA PASIFIK DALAM PUSARAN GLOBALISASI - Haripin, Muhamad (Jurnal Penelitian Politik, 2011)
Globalization has dramatically changed state s threat perception and defence pas tune Furthermore newplayers and newforms of interconnectedness between state actors and non state actors shape the contemporarylandscape of international security Throughout Asia Pacific nation states have started to realize that it is lessrelevant to focus only on traditional military invasion Other challenges e g transnational crime and terrorismare awaitingfor government s swift yet effective response